Implicature In Some Selected Hollywood Films’ Scenes (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to investigate implicature in Hollywood films. It is limited to different types of Hollywood films, namely:  comic films and   tragic films at three various selected periods: old period, middle period and modern period. The study consists of five sections :  the preliminaries  ( which presents the fundamentals of the study ) , the framework of the study  ( which views the theoretical background  on which the study is based ) , methodology and material ( which explains the basic procedures and the material that are used to conduct the study ) , the findings and discussion ( which displays the results of implicature in the selected scenes accompanied with discussion and examples ) and finally  the conclusions which are drawn in the light of  the findings.